1993
DOI: 10.1172/jci116375
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat increases high density lipoprotein (HDL) levels both by increasing the transport rates and decreasing the fractional catabolic rates of HDL cholesterol ester and apolipoprotein (Apo) A-I. Presentation of a new animal model and mechanistic studies in human Apo A-I transgenic and control mice.

Abstract: IntroductionIn humans, diets high in saturated fat and cholesterol raise HDL-cholesterol (HDL-C) levels. To explore the mechanism, we have devised a mouse model that mimics the human situation. In this model, HuAITg and control mice were studied on low fat (9% cal)-low cholesterol (57 mg/1,000 kcal) (chow) and high fat (41% cal)-high cholesterol (437 mg/1,000 kcal) (milk-fat based) diets. The mice responded to increased dietary fat by increasing both HDL-C and apo A-I levels, with a greater increase in HDL-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
70
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 39 publications
15
70
0
3
Order By: Relevance
“…9 Monolayers of cerebral microvascular endothelial cells exposed to Ang II also exhibit an increased permeability that is dependent on Ang II type-1 receptors. 29 Like previous studies, 30 we observed an increased plasma HDL concentration in mice placed on a high-fat, cholesterol-enriched diet. Our study also provides two lines of evidence that are consistent with a role for HDL in mediating the antiinflammatory and antithrombogenic effects of HCh.…”
Section: Discussionsupporting
confidence: 86%
“…9 Monolayers of cerebral microvascular endothelial cells exposed to Ang II also exhibit an increased permeability that is dependent on Ang II type-1 receptors. 29 Like previous studies, 30 we observed an increased plasma HDL concentration in mice placed on a high-fat, cholesterol-enriched diet. Our study also provides two lines of evidence that are consistent with a role for HDL in mediating the antiinflammatory and antithrombogenic effects of HCh.…”
Section: Discussionsupporting
confidence: 86%
“…FPLC analysis of plasma from hypercaloric diet-fed mice showed that difference in VLDL accounted for the different plasma triglyceride levels between Pla2g1b +/+ and Pla2g1b Ϫ / Ϫ mice. Additionally, the Pla2g1b Ϫ / Ϫ mice also did not display elevated plasma HDL levels (data not shown), which are typically observed in wild-type mice after high-fat feeding ( 28 ). The mechanism underlying the differences in plasma lipid levels between Pla2g1b +/+ and Pla2g1b Ϫ / Ϫ mice was explored by comparing hepatic VLDL production rates in these animals under both basal and hypercaloric dietary conditions.…”
Section: Pla2g1bmentioning
confidence: 92%
“…The plasma decay curve was used to fit an exponential curve by computer analysis. The fractional catabolic rate (FCR) was calculated as the inverse of the area under the decay curves as described (18,19).…”
Section: Nmr Lipoprotein Analysismentioning
confidence: 99%